2020
DOI: 10.4103/jmau.jmau_48_20
|View full text |Cite
|
Sign up to set email alerts
|

Transformation to virtual training during COVID-19 pandemic: Case report from a low resources' country

Abstract: Many challenges had faced medical schools worldwide after the beginning of the COVID-19 pandemic. From these challenges, training of the next generation of physicians and academic staff. Adoption of online education and training with getting the benefit of technology had introduced. Egypt has another special challenge, which is the adoption of a new undergraduate competency-based program since September 2018. Hence, there is a necessity to complete the ongoing capacity building of the academic staff regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…This is crucial, given that some studies observed that a critical challenge during the pandemic was the disruption of education and training. This claim is made by Sadek and Kora (2020), whose attendance at workshops, conferences and training courses halted in almost all countries worldwide. They argued that the pandemic seriously disrupted some academic courses and that teachers and trainers who were less versed in technology found it challenging to teach through the Internet (Sadek and Kora, 2020).…”
Section: Results Of the Scenario-based Tabletop Exercisementioning
confidence: 99%
“…This is crucial, given that some studies observed that a critical challenge during the pandemic was the disruption of education and training. This claim is made by Sadek and Kora (2020), whose attendance at workshops, conferences and training courses halted in almost all countries worldwide. They argued that the pandemic seriously disrupted some academic courses and that teachers and trainers who were less versed in technology found it challenging to teach through the Internet (Sadek and Kora, 2020).…”
Section: Results Of the Scenario-based Tabletop Exercisementioning
confidence: 99%
“…Results of this study are generally consistent with prior international work documenting the benefits of virtual training as part of behavioral health and medical education. A 2020 study by Sadek and Kora described how medical schools in Egypt had to rapidly adopt online education and training during the early months of the pandemic, and found that students reported high satisfaction with virtual training with no complaints about the quality of instruction [ 25 ]. Similarly, Khursid and colleagues’ rapid narrative review of 19 studies argued that rather than viewing the pandemic as a disruption to education and training, it should be considered an opportunity to improve distance learning techniques and enhance educational delivery after the relaxation of social distancing orders [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of video conferencing as an educational medium was rapidly adopted with the ongoing travel limitations imposed by SARS CoV2. The project benefitted from this and believe that video conferencing is a suitable alternative for Training of Trainers [ 14 ]. One of the roles of IPHCE is to increase capacity of primary health care (PHC) systems within Ethiopia.…”
Section: Introductionmentioning
confidence: 99%